A Comparative Whole Genome Sequence Analysis Leads to Identification of Repeat-Associated Evolutionarily Conserved miRNAs in Bombyx mori (Lepidoptera: Bombycidae). Issue 3 (8th June 2019) - Singh, Jyoti; Ambi, Uddhav B
Abstract: MicroRNAs (miRNAs) are evolutionarily conserved small noncoding RNAs, which play important regulatory roles in various biological processes. In this study, we have developed a computational approach for detecting conserved miRNAs based on comparison of whole genome sequences of closely related species by considering various key features of experimentally validated miRNAs. By applying this approach, we have identified 34 new miRNAs from Bombyx mori (L.), which are also conserved in Drosophila melanogaster (Diptera: Drosophilidae) and Anopheles gambiae (Diptera: Culicidae). Most of these miRNAs were associated with repeat region of the genome. We did an expression analysis of the 34 newly predicted miRNAs and found that 30 of these miRNAs are expressing in different tissues of B. mori. Besides, we have also predicted the putative targets of these miRNAs in B. mori based on several known characteristic features of miRNA::mRNA duplexes and found that these targets include diverse range of functions, suggesting multiple layers of gene regulation of various important biological processes.